Chromium in food products - Sykuła-Zając, Anna; Pawlak, Anna (Biotechnology and Food Science, 2012)
Chromium plays an important role in human and animal bodies. According to the oxidation state chromium can be advantageous for human health and, simultaneously possesses toxic properties. In this work the studies concerning the chromium content in the total and Cr (VI) forms in selected and frequently used during breakfast food products were presented. The largest quantities of the metal occur in raw cereal products (non-roasted buckwheat or brown rice bread) and herbs such as garlic or mint. The lowest chromium contents were observed in raw and UHT milk samples.